Evaluation of Sectio Cesaria Response Time to Maternal and Neonatal Outcomes in Severe Preeclampsia - Eclampsia Patients - Syahbana, Khalda Fakhirah; Dwimartyono, Fendy; Sirajuddin, Nur Fatimah; Haeriyanty, Haeriyanty; Harahap, Wirawan (Journal La Medihealtico, 2024)
This research is finding out an overview of the response time evaluation of Sectio Cesaria in patients with severe Pre-eclampsia - Eclampsia at Sitti Khadijah 1 Muhammadiyah Hospital Makassar Branch. Severe preeclampsia and eclampsia are complications in pregnancy and childbirth that increase maternal and infant morbidity and mortality rates. To prevent the problem of eclampsia, early management of preeclampsia must be carried out properly. Cesarean sections are classified into two categories, namely SC categories 1 and 2. Category 1 Caesarean sections are SCs that must be carried out as soon as possible and most decisions must be taken within 30 minutes, namely in cases that immediately threaten the lives of the mother and baby, such as fetal distress, non-reassuring fetal status, antepartum hemorrhage, and the threat of uterine rupture. While SC category 2 is one that endangers the mother and fetus but not immediately, such as two previous CS, dystocia, hypertension in pregnancy, premature rupture of membranes, breech position, failed induction, bad obstetric history, macrosomia, cephalopelvic disproportion, facial presentation, and most decisions must be taken within 75 minutes. This research method is observational research using a cross sectional approach. The results of this research is maternal outcome most affected by SC response time <75 minutes is postoperative ICU care, and the most influential neonatal outcome is the APGAR Score. Based on the research results, it can be concluded that response time has a significant influence on maternal and neonatal outcomes in patients with severe preeclampsia - eclampsia.